2020
DOI: 10.3389/fmicb.2020.587979
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacterial Supplementation on Black Soldier Fly Growth and Development at Benchtop and Industrial Scale

Abstract: Historically, research examining the use of microbes as a means to optimize black soldier fly (BSF) growth has explored few taxa. Furthermore, previous research has been done at the benchtop scale, and extrapolating these numbers to industrial scale is questionable. The objectives of this study were to explore the impact of microbes as supplements in larval diets on growth and production of the BSF. Three experiments were conducted to measure the impact of the following on BSF life-history traits on (1) Arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 67 publications
(67 reference statements)
0
36
1
Order By: Relevance
“…Our method of incorporating the residue-derived inoculums back into the substrate did not improve the rearing performance. This is in contrast with previous studies that showed clear improvement in rearing efficiencies with the addition of pure-culture bacteria or defined bacterial mixtures (Kooienga et al, 2020;Rehman et al, 2019;Somroo et al, 2019;Xiao et al, 2018;Yu et al, 2011), and even the rudimentary use of fermentate is ubiquitous in accelerating the fermentation of foods. A possible explanation for this result is that the residues did not include probiotic bacteria.…”
Section: Effect Of Residue-derived Bacterial Inoculums (Experiments 2)contrasting
confidence: 95%
See 3 more Smart Citations
“…Our method of incorporating the residue-derived inoculums back into the substrate did not improve the rearing performance. This is in contrast with previous studies that showed clear improvement in rearing efficiencies with the addition of pure-culture bacteria or defined bacterial mixtures (Kooienga et al, 2020;Rehman et al, 2019;Somroo et al, 2019;Xiao et al, 2018;Yu et al, 2011), and even the rudimentary use of fermentate is ubiquitous in accelerating the fermentation of foods. A possible explanation for this result is that the residues did not include probiotic bacteria.…”
Section: Effect Of Residue-derived Bacterial Inoculums (Experiments 2)contrasting
confidence: 95%
“…isolated intestinal bacteria and showed a positive influence on the larval growth after the addition of Escherichia coli and Bacillus licheniformis to the substrate, but not Stenotrophomonas maltophilia. Similarly,Kooienga et al (2020) observed that the growth rate increased with Arthrobacter AK19 and Rhodococcus rhodochrous 21198, but the addition of Bifidobacterium breve to the substrate had adverse effects. Similarly,Mazza et al (2020) inoculated chicken manure with pure-culture bacteria and bacterial mixtures isolated from eggs and digestive tracts.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…As their metabolic complexity and ability is intense, they have the potential to dramatically affect the physiological condition of the insect. Revealing these metabolic interactions may help to increase the rearing efficiency of insects, such as the BSF, which is currently being reared at large scales as an alternative protein source (25).…”
Section: Discussionmentioning
confidence: 99%